Bureaucracy Reform And Implementation Of Good Government And Implications On Employee Performance And Service Quality (Study at the Regional Revenue and Finance Office of Palopo City) - Abdul Rahman; M. Risal; Salju (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to examine and analyze the phenomena of the impact of bureaucratic reform, leadership skills, and the application of good governance on employee performance and its implications for service quality. This research was conducted at the Regional Revenue and Finance Office of Palopo City. The number of samples in this study were 65 employees. The research method used is descriptive quantitative with data collection techniques using a questionnaire. The independent variables consist of bureaucratic reform (X1), leadership skills (X2), and employee performance (X3 ) as intervening variables and the dependent variable is service quality (Y). The analyst used to test is to use the help of the SPSS application. The results showed that bureaucratic reform had no effect on service quality , leadership skills had a significant effect on employee performance, and employee performance did not significantly affect service quality.